THE EFFECT OF IMPACT ANGLE ON THE BALLISTIC PERFORMANCE OF TC4 TARGET AGAINST THE IMPACT OF HEMI-SPHERICAL PROJECTILE - ZHANG TieChun; WANG LuJun; HU Ang; PENG Jie; AN JingDan (Jixie qiangdu)
In order to study the ballistic resistance of TC4 titanium alloy under different impact angle,the experimental study on the high velocity impact of hemi-spherical projectile on TC4 titanium alloy target plate by light gas gun was carry out. The ballictic limit and failure mode was obtained. Based on experimental conditions,simulation model and material parameters had been validating through ABAQUS and the influence of impact angle on the ballistic resistance of TC4 titanium alloy had been further analyzing. The research result indicate that the main failure mode of TC4 titanium alloy against hemi-spherical projectile is petal-shaped failure caused by tensile shear and ductile holing; There exists an easiest penetration angle under which the projectile can penetrate the TC4 titanium alloy target most easily; The impact resistance of the target plate is closely related to the failure mode which is different under varying impact angel.